Mature teratoma of the mediastinum in children: A case revealed by persistent chest pain - S.P. Kebalo, MD; D. Lamboni, MD; K.M. Guedenon, MD; K. Amegbor, MD; K. Gnassingbe, MD (Elsevier, 2022)
Mature teratoma is a primary germ cell tumor frequently revealed during childhood in its sacrococcygeal and gonadal location, and rarely in the mediastinal location. The mode of the revelation of this tumor in the mediastinum ranges from incidental discovery to acute respiratory distress syndrome. We report the management of a case of mature mediastinal teratoma in a 10-year-old girl revealed by persistent chest pain evolving for 16 days. This observation will allow us to review the epidemiological, diagnostic, therapeutic, and prognostic aspects of this affection.